PENGEMBANGAN SDM DALAM MENINGKATKAN PRODUKTIVITAS KINERJA KARYAWAN di BPBD SUBANG - Nike Amalia; Fitria Zulfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of Human Resource Development (HRD) in improving employee work productivity at the Regional Disaster Management Agency (BPBD) of Subang Regency. Human resource development is a crucial aspect of organizational management because the quality of employees directly influences the effectiveness of organizational performance and public service delivery, particularly in disaster management, which requires high levels of preparedness, competence, and professionalism. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the Head of General Affairs and Personnel, personnel staff, and field officers at BPBD Subang Regency.The findings reveal that HRD programs at BPBD Subang Regency are implemented through various activities, including disaster management training, technical guidance programs, seminars, continuing education, and collaborations with the National Disaster Management Agency (BNPB), Provincial BPBD, and higher education institutions. These programs contribute significantly to improving employees’ technical competencies, administrative capabilities, discipline, work motivation, and preparedness in responding to emergency situations. Furthermore, the HRD strategies applied include strengthening technical competencies, conducting community-based disaster awareness programs through the Disaster Resilient Village (Destana) initiative, and implementing job analysis to identify employees’ development needs more effectively.The impact of HRD initiatives is reflected in increased employee productivity, faster disaster response, improved interdepartmental coordination, and enhanced public service quality. However, several challenges remain, including limited training budgets, an imbalance between the number of employees and workload demands, insufficient supporting facilities, and relatively slow administrative processes. Therefore, more innovative, systematic, and sustainable HRD strategies are needed to ensure continuous improvement in employee productivity and organizational performance. This study confirms that human resource development is a strategic factor in enhancing the productivity, competence, and professionalism of BPBD employees in carrying out disaster management responsibilities effectively and efficiently.